Training on pricing, profit, and packaging Dian Kristawati product, in Kemoning Bali - Purwaningtyas Kusumaningsih; Ni Made Erpia Ordani Astuti; Rai Gina Artaningrum (Universitas Pendidikan Indonesia, 2026)
The Dian Kristawati women's group, located in Kemoning Village, Klungkung, Bali, has developed processed okara products in various forms, including chips, cakes, brownies, cookies, and nuggets. No other okara-based products are being sold in Klungkung Regency, so the partners aim to create packaging labels that provide information and identify the uniqueness of okara products, thereby increasing awareness and sales. This service aims to assist in creating labels for the five partner products and in adapting them to the partners' wishes and conditions. The methods used in this project are participatory, involving partners in creating the packaging labels, as well as qualitative and quantitative methods, namely determining partners' preferences for product labeling based on interview results to identify their needs. Technology development involved assisting with using the Canva program to create packaging labels for partner products. As a result of this community service, the partners now have five packaging labels containing information about the uniqueness of the products, the identity of the partners with the name Dian Kristawati Tresna Asih Klungkung, and the partners' contact details and social media addresses, which contain information about the production and types of okara products. Abstrak Kelompok wanita Dian Kristawati berlokasi di Desa Kemoning, Klungkung Bali memiliki pengembangan produk olahan okara berupa keripik, bolu, brownies, kukis dan nuget. Penjualan produk di kabupaten Klungkung berbahan okara belum ada yang membuat olahan serupa, oleh karena itu mitra ingin membuat label kemasan yang dapat memberikan informasi dan identitas tentang kekhasan produk olahan okara supaya dapat dikenal dan meningkatkan penjualan. Tujuan pengabdian ini adalah untuk memberikan pendampingan dalam membuat label kelima produk mitra dan disesuaikan dengan keinginan serta kondisi mitra. Metode yang digunakan dalam pengabdian ini adalah partisipatif dengan melibatkan mitra dalam membuat label kemasan, kualitatif dan kuantitatif yaitu mengetahui keinginan mitra tentang kebutuhan labeling produk berdasarkan hasil wawancara untuk mengetahui kebutuhan mitra. Pengembangan teknologi dengan memberikan pendampingan penggunaan program Canva dalam membuat label kemasan produk mitra. Hasil dari pengabdian ini mitra memiliki lima label kemasan berisikan informasi kekhasan produk, identitas mitra dengan nama Dian Kristawati Tresna Asih Klungkung dan kontak serta alamat media sosial mitra didalamnya berisikan tentang informasi pembuatan, dan jenis olahan okara. Kata Kunci: identitas produk; informasi produk label; kemasan